2018
DOI: 10.1111/eje.12378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a preclinical practice of tooth preparation using digital training system: A randomised controlled trial

Abstract: The digital training system with OPRS and RDTES might be a good alternative to the traditional training method in the preclinical course of dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 24 publications
(39 reference statements)
0
63
0
Order By: Relevance
“…Their baseline data of practical skills of ceramic crown preparation were collected via the RDTES under the same conditions. Following completion of the practical work on the phantom head, the RDTES assessed the results based on the pre‐defined assessment criteria . Then, the students were requested to perform the online virtual learning course on the VLNP, involving reading the operational instructions and pre‐defined criteria of preparing a ceramic crown.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their baseline data of practical skills of ceramic crown preparation were collected via the RDTES under the same conditions. Following completion of the practical work on the phantom head, the RDTES assessed the results based on the pre‐defined assessment criteria . Then, the students were requested to perform the online virtual learning course on the VLNP, involving reading the operational instructions and pre‐defined criteria of preparing a ceramic crown.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the tooth preparation were assessed by the RDTES based on the pre‐defined assessment criteria, which included two parts: process and outcome assessments of the practice (Table ). The process assessment consisted of the preparation sequence and instrument selection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recently, the evaluation software of fixed dental practice evaluation using computer-aided design and computer-aided manufacturing (CAD/CAM) has been widely used. [4][5][6][7][8][9][10] Compared to traditional learn-ing tools, color mapping for tooth preparation using scanning can provide useful information to students concerning the overall reduction amount. Renne et al 2 have reported that evaluation using CAD/CAM software has an important advantage of enabling students to work independently.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported that evaluation using CAD/CAM software is objective and accurate. [4][5][6][7][8][9][10][11][12] However, another report has indicated that evaluation of clinically critical errors is not possible using software alone as an evaluation tool. 1 In addition to digital assessment, students should be able to perform self-assessment on their own.…”
Section: Introductionmentioning
confidence: 99%